TEACHER ROLE IN FORMATION POLITENESS OF STUDENT LEARNING PROCESS - Wahyuni Oktavia; Safrihady Safrihady (JETL (Journal of Education, Teaching and Learning), 2016)
Language as a communication tool has an important role in human interaction. Language can be used to convey ideas, ideas, feelings, desires, and so forth to others. To be able to communicate well certainly should be able to adjust the language used. One of the main functions of communication is to maintain the continuity of the relationship between the narrator and hearer. Language is an important pillar in the formation of character, in addition to religious education and moral education. In education, teachers must have pedagogical, professional, personal, and social. Teachers who have a good competence speech acts certainly have a good and well mannered to students. In the learning process, teachers and students communicate in give and receive course materials. The learning process is certainly not only provides knowledge alone, but give the values of character to students. In this case, the teacher must have a principle that must be controlled properly, correctly and precisely. Thus, teachers are expected to master the communication and understanding the principles of politeness in speaking well and correctly. The goal is a description of a form of politeness in the learning process. This research is a descriptive study which seeks to describe a form of politeness in the learning process. Data collection method used is the method refer to the data collection techniques are 1) recording technique using a tape recorder, and 2) technical note on the data card. Furthermore, methods of data analysis using pragmatic frontier.